The “Boomerang” iliac crest flap for hemimandible reconstruction in rare Paget's Osteosarcoma: Case report and systematic literature review - Olindo Massarelli; Samira Bucelli; Simone Benedetti (Oral Oncology Reports)
Paget's bone disease is a rare disease affecting the skeleton, inducing deformity and weakness of the affected bones and involving the splanchnocranium in only 8–23 % of all cases. One of the most severe and uncommon complications is the malignant transformation into osteosarcoma, occurring in 1.4 % of all cases of Paget's disease and arising in the mandible in extremely rare cases, with only 18 reports described in the literature.The authors present a rare case of a large mandibular Paget's osteosarcoma in a female patient, highlighting the planning and surgical tips for surgical resection and hemimandibular reconstruction with a “boomerang” shaped osteo-myo-cutaneous (OMC) iliac crest flap. By taking advantage of the specific curvature and peculiar bone height of the OMC iliac crest flap, it was possible to restore good symmetry of the contour of the facial lower third, perfectly matching to the abnormal shape of the healthy hemimandible affected by Paget's disease.